Advancing AI: A Comprehensive Study of Novel Machine Learning Architectures - Boya Marqas , Ridwan; Saman M. Almufty,; Renas R. Asaad,; Tamara Saad mohamed, Dr. (International Journal of Scientific World, 2025)
The rapid evolution of machine learning (ML) and artificial intelligence (AI) has led to groundbreaking advancements in computational models, empowering applications across diverse domains. This paper provides an in-depth exploration of advanced ML architectures, including transformers, Graph Neural Networks (GNNs), capsule networks, spiking neural networks (SNNs), and hybrid models. These architectures address the limitations of traditional models like convolutional and recurrent neural networks, offering superior accuracy, scalability, and efficiency for complex data. Key applications are discussed, ranging from healthcare diagnostics and drug discovery to financial fraud detection, autonomous systems, and logistics optimization. Despite their potential, these architectures face challenges such as computational overhead, scalability, and interpretability, necessitating interdisciplinary solutions. The paper also outlines future directions in edge computing, explainable AI, quantum machine learning, and few-shot learning, emphasizing the transformative role of advanced ML architectures in reshaping AI’s future.